Validation of accelerometers and gyroscopes to provide real-time kinematic data for golf analysis - Fitzpatrick, K.; Anderson, R. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
Golfers continually demand more information about their performance and require immediate feedback on their swing. This research attempts to measure the pitch and yaw angle of the clubhead at ball-contact and compare this to the same angle at shot set-up. Acceleration of the clubhead at ball-contact is also measured. These three variables have been linked to golfing performance in the literature. For the research two gyroscopes and one dual axis accelerometer were incorporated with a putter head. One gyroscope was positioned on the head of the club to measure deviations occurring between the yaw angle at set-up and the yaw angle at ball contact. A second gyroscope was positioned to measure deviations between the pitch angle at shot set-up and the pitch angle at ball contact. Each gyroscope also provides angular velocities of the club throughout the swing. To measure the clubhead acceleration (a) an accelerometer was positioned on the clubhead parallel to the movement. The system and methodology has been verified and tested for both accuracy and reliability in the field, it is those results that are presented here. Several testing techniques were used to ensure the data obtained from the sensors was accurate and compared well with kinematic data obtained from a motion analysis system. The reported RMSD error existing between the angle data obtained from the sensors and the motion analysis system was 0.20 for both the yaw and pitch angle over any two second period (sufficient for a golf stroke). The accelerometers illustrated potential benefit for use as feedback tool but proved to be inadequate as a method for deriving velocities or displacements. The output from the gyroscopes and accelerometer may be displayed in a manor such that it is a feasible means for giving valuable feedback to a golfer.